KOORDINASI PEMELIHARAAN KUALITAS MUTU GAMBIR NAGARI LUBUK ALAI KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Satria, Jaka; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Gambier is a kind of sap that has been compacted from the processing of leaves and branches of the gambier plants. The Gambier product is a hot water extract from the gambier leaves and branches that are already sedimentated and then molded and dried. Indonesia is the most important supplier of world gambier needs. However, the way of the cultivation or the processing is still traditional and moreover the farmer who mixed the gambier with soil and another material made a bad effect for the quality of the gambier. The method that is used for this study is purposive sampling, the data source that is used in this study include primary and secondary data, the location of this study was conducted in Kenagarian Lubuk Alai, Kapur IX District of Lima Puluh Kota Regency, the research informan Wali Nagari Kenagarian Lubuk Alai, Secretary Nagari Kenagarian Lubuk Alai, Kaur Kenagarian Lubuk Alai, Wali Jorong Kenagarian Lubuk Alai, dan Badan Permusyawaratan Kenagarian Lubuk Alai. The concept theory that is used by the researcher was coordination theory by Hendayaningrat in Moekijat which is consist of: responsibilities, processes, regularly regulations, unity of actions, coordination objectives. This study used qualitative research method with reviewed the data with qualitative descriptive, the data collecting technique was interviews, observations and documentation. To guarantee the validity of the data, the researcher used triangulation of data sources. From the result of the study, it is known that the coordination of gambier quality control Nagari Lubuk Alai has been categorized good. It can be improved from the increasing of the gambier quality Nagari Lubuk alai and can be seen that from five indicator that was taken by the researcher, four indicator went well and one indicator still not good. The factor that interfere The Coordination of Gambier Quality Control in Nagari Lubuk Alai Kapur IX District of Lima Puluh Kota Regency was: market, Government Regulation, Individual. Keyword : Coordination and Gambier